Highly Osmotic Oxidized Sucrose-Crosslinked Polyethylenimine for Gene Delivery Systems - Jaehong Park; Kyusik Kim; Sohee Jeong; Migyeom Lee; Tae-il Kim (MDPI AG, 2021)
In this work, highly osmotic oxidized sucrose-crosslinked polyethylenimine (SP2K) polymers were developed for gene delivery systems, and the transfection mechanism is examined. First, periodate-oxidized sucrose and polyethylenimine 2K (PEI2K) were crosslinked with various feed ratios via reductive amination. The synthesis was confirmed by 1H NMR and FTIR. The synthesized SP2K polymers could form positively charged (~40 mV zeta-potential) and nano-sized (150-200 nm) spherical polyplexes with plasmid DNA (pDNA). They showed lower cytotoxicity than PEI25K but concentration-dependent cytotoxicity. Among them, SP2K7 and SP2K10 showed higher transfection efficiency than PEI25K in both serum and serum-free conditions, revealing the good serum stability. It was found that SP2K polymers possessed high osmolality and endosome buffering capacity. The transfection experiments with cellular uptake inhibitors suggest that the transfection of SP2K polymers would progress by multiple pathways, including caveolae-mediated endocytosis. It was also thought that caveolae-mediated endocytosis of SP2K polyplexes would be facilitated through cyclooxygenase-2 (COX-2) expression induced by high osmotic pressure of SP2K polymers. Confocal microscopy results also supported that SP2K polyplexes would be internalized into cells via multiple pathways and escape endosomes efficiently via high osmolality and endosome buffering capacity. These results demonstrate the potential of SP2K polymers for gene delivery systems.